A Literature Review on Ambidextrous Leadership to Strengthen Organizations' Dynamic Capabilities - Jauhari, Angel Permata; Lantu, Donald Crestofel; Purwanto, Jaka (Integrasi Sains Media, 2026)
Organizations operating within increasingly dynamic and volatile environments confront the perennial challenge of sustaining operational efficiency while simultaneously fostering innovation to ensure long-term competitiveness. Within contemporary leadership discourse, ambidextrous leadership has emerged as a pivotal approach for organizations to navigate an ever-changing future. This study synthesizes 21 recent scholarly works (spanning 2020–2025) to elucidate the conceptual framework of ambidextrous leadership and its role in fortifying organizational dynamic capabilities, ultimately proposing an integrative framework of the two constructs. A systematic literature review guided by the PRISMA methodology finds that ambidextrous leadership facilitates the execution of the tripartite core of dynamic capabilities: sensing, seizing, and reconfiguring. Consequently, this paper provides novel insights into the nexus between ambidextrous leadership and dynamic capabilities, transcending the conceptual isolation of these constructs prevalent in prior scholarship.